Indirect Electrochemical Oxidation of Phenol Using Rotating Cylinder Reactor - Abbas, Ammar S.; Hafiz, Mohammad H.; Salman, Rasha H. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Indirect electrochemical oxidation of phenol and its derivatives was investigated by using MnO2 rotating cylinder electrode. Taguchi experimental design method was employed to find the best conditions for the removal efficiency of phenol and its derivatives generated during the process. Two main parameters were investigated, current density (C.D.) and electrolysis time. The removal efficiency was considered as a response for the phenol and other organics removal. An orthogonal array L16, the signal to noise (S/N) ratio, and the analysis of variance were used to test the effect of designated process factors and their levels on the performance of phenol and other organics removal efficiency. The results showed that the current density has the higher influence on performance of organics removal while the electrolysis time has the lower impact on the removal performance. Multiple regressions was utilized to acquire the equation that describes the process and the predicted equation has a correlation coefficient (R2) equal to 98.77%. The best conditions were found to get higher removal efficiency. Removal efficiency higher than 95% can be obtained in the range of C.D. of 96-100 mA/cm2 and electrolysis time of 3.2 to 5 h. The behavior of the chemical oxygen demand (COD) mineralization denotes to a zero order reaction and the rate of reaction controlled by active chlorine reaction not by mass transfer of phenol towards the anode.